1097 Activated Protein C Decreases Endotoxin-Induced Inflammatory Responses in Infants with Neonatal Encephalopathy. (October 2012) - Eliwan, HO; O'Hare, FO; Sweetman, D; Watson, W; O'Neill, A; Molloy, EJ
Abstract : Introduction: Infection and inflammation can be antecedents of neonatal encephaloapthy (NE) and increase the risk of neurological sequelae. Activated protein C (APC) has anticoagulant and anti-inflammatory effects and provides neuroprotection in ischemic brain and spinal cord injury. Aims: To examine neutrophil and monocyte responses to Lipopolysaccharide (LPS) in infants with NE (n= 22) and also the effect of APC compared with healthy adult controls (n=15). Methods: Whole blood was incubated with LPS +/-APC and TLR4, CD11b expression, and reactive oxygen intermediate (ROI) release from neutrophils and monocytes was examined by flow cytometry. Results: Neutrophil and monocyte CD11b expression was significantly increased in response to LPS in adults controls (p<0.001) and NE infants (p<0.001). However infants with NE were LPS-hyporesponsive compared to adults control and APC did not reduce this effect. Neutrophil TLR4 expression was significantly increased in response to LPS in NE infants on D3 compared to adults (p<0.001) and has been reduced by APC (p=0.03). LPS induced monocyte TLR4 was only significantly increased in NE infants D7 (p<0.001). Neutrophil ROI was significantly increased in Adults (p<0.001) and NE infants on D3 (p=0.021) following LPS and this response were significantly reduced by APC. Conclusion: Neutrophil activation and production of ROI may mediate tissue damage in NE infants. APC modified LPS responses in adults and NE infants on D3 of life. APC may reduce the inflammatory responses secondary to hypoxia and possibly benefit these patients at high risk of inflammatory multiorgan dysfunction.